PENGARUH INFLASI DAN NILAI TUKAR (KURS US TERHADAP RUPIAH) TERHADAP HARGA DAN OMZET PENJUALAN TOYOTA KIJANG INNOVA TIPE G DI JAWA TENGAH DAN DAERAH ISTIMEWA YOGYAKARTA - Dinda Rima Fatharani; Ngatno Ngatno (Universitas Diponegoro, 2016)
Inflation, exchange rate, and price are the keys to achieve sales turnover of a company. ToyotaKijang Innova Type G is a multipurpose vehicle which is popular in demand because it isfunctional and still affordable. Toyota Innova is PT Astra Motor’s product is the result ofcooperation between PT Astra International and PT Toyota Motor Corporation. The successful of acompany can be measured by many things. One of those things is sales turnover. That is why weneed to analyze economic factors that influence price to make sales target and determine the stepsto control the market.This type of research is using explanatory research in 2010 until 2015 with 72 data inmonth for every variable. The data is collected by primary and secondary method. Simple linearregression, multiple linear regression, path analysis, and Sobel method are used for the analysiswith PASW Program 18.0.The result shows that inflation and exchange rate have partial and simultaneouseffect to sales turnover by the price of Toyota Kijang Innova Type G. Exchange rate variablehas greater effect than inflation. Price has become partial mediation variable for inflation andexchange rate.Business agents and the government are suggested to take care of economic stabilityand improve economy growth to keep inflation and exchange rate stable, so that the price stillaffordable for consumers.The suggestions are for business agent and the government should take care ofeconomic stability and improve economy growth to keep inflation and exchange rate stable, so theprice still affordable for consumers.